2020
DOI: 10.21037/apm-20-1478
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing injection in the treatment of COVID-19: a retrospective case-control study

Abstract: Background: Neither a vaccine nor specific therapeutic drugs against 2019 novel coronavirus have been developed. Some studies have shown that Xuebijing injection (XBJ) can exert an anti-inflammatory effect by inhibiting the production of interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), and other cytokines.This study aimed to investigate the effect of XBJ on coronavirus disease 2019 (COVID-19) and its effects on IL-6 and tumor necrosis alpha TNF-α.Methods: A total of 42 patients, who were diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…In total, we analyzed 48 studies 3–7,20–60 recruiting 4,704 patients with COVID‐19. Of these, 29 20,22–29,31,34–36,39,40,49–62 were observational studies with a control group, and 19 3–7,30,32,33,37,38,41–48,63 were RCTs included in the final analysis. Of these participants, 2,696 had been assigned to receive CHM as an adjuvant medicine, and 2,008 receive standard pharmacotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, we analyzed 48 studies 3–7,20–60 recruiting 4,704 patients with COVID‐19. Of these, 29 20,22–29,31,34–36,39,40,49–62 were observational studies with a control group, and 19 3–7,30,32,33,37,38,41–48,63 were RCTs included in the final analysis. Of these participants, 2,696 had been assigned to receive CHM as an adjuvant medicine, and 2,008 receive standard pharmacotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The other 13 studies 5–7,32,33,37,38,41–46 did not mention the blinding of patients and personnel. Table 3 showed the NOS details for 29 observational studies 20,22–29,31,34–36,39,40,49–62 . Eight observational studies 20,22,24,26,34,49,50,57 were judged to be of moderate methodologic quality, subject to the unsatisfying risk of bias mostly owing to the lack of adequacy of follow up and completing accounting for observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also attenuates pulmonary injury by reducing oxidative stress and proinflammatory damage in rats with heat stroke (Chen et al, 2017). In a recent study, it showed benificial effect against inflammatory markers and disease outcome of coronavirus disease 2019 (Guo et al, 2020;Long et al, 2020). The main pharmacological effects of XueBiJing might be summarized as follows: (1) antagonizing endotoxin; (2) inhibiting inflammatory cytokines; (3) decreasing oxidative stress; (4) regulating immune function; (5) improving the balance of coagulation; (6) protecting organ damage.…”
Section: Introductionmentioning
confidence: 98%